(untitled) (diségno, 2020)
Francesca Fatta in the Preface of the book Didattica del segno, percorsi pedagogici by Starlight Vattano, published by Franco Angeli in the open-access edition, writes that children drawing “can visibly and durably express the imagination, emotion, sensation and thought of the person who performs it, almost as if to draw a tangible sign of himself” (read more).